Diplomacy: concepts, actors, organs, process and rules - Kappeler, Dietrich; Mwagiru, Makumi; Odera, Josephine (Wab Artistics 2010, 1915)
Blackstone Theatre, Seventh Street, near Michigan Boulevard, Blackstone Theatre Co., lessee, directors Charles Frohman, Marc Claw, Abraham L. Erlanger, William Harris, Harry J. Powers, Harry J. Powers, manager, Edwin Wappler, business manager. Charles Frohman presents William Gillette, Blanche Bates, Marie Doro in a play in four acts "Diplomacy," by Victorien Sardou.
Includes index
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Diplomacy